Drosophila Spidey/Kar Regulates Oenocyte Growth via PI3-Kinase Signaling. - Einat Cinnamon; Rami Makki; Annick Sawala; Leah P Wickenberg; Gary J Blomquist; Claus Tittiger; Ze'ev Paroush; Alex P Gould (PLoS Genetics)
Cell growth and proliferation depend upon many different aspects of lipid metabolism. One key signaling pathway that is utilized in many different anabolic contexts involves Phosphatidylinositide 3-kinase (PI3K) and its membrane lipid products, the Phosphatidylinositol (3,4,5)-trisphosphates. It remains unclear, however, which other branches of lipid metabolism interact with the PI3K signaling pathway. Here, we focus on specialized fat metabolizing cells in Drosophila called larval oenocytes. In the presence of dietary nutrients, oenocytes undergo PI3K-dependent cell growth and contain very few lipid droplets. In contrast, during starvation, oenocytes decrease PI3K signaling, shut down cell growth and accumulate abundant lipid droplets. We now show that PI3K in larval oenocytes, but not in fat body cells, functions to suppress lipid droplet accumulation. Several enzymes of fatty acid, triglyceride and hydrocarbon metabolism are required in oenocytes primarily for lipid droplet induction rather than for cell growth. In contrast, a very long chain fatty-acyl-CoA reductase (FarO) and a putative lipid dehydrogenase/reductase (Spidey, also known as Kar) not only promote lipid droplet induction but also inhibit oenocyte growth. In the case of Spidey/Kar, we show that the growth suppression mechanism involves inhibition of the PI3K signaling pathway upstream of Akt activity. Together, the findings in this study show how Spidey/Kar and FarO regulate the balance between the cell growth and lipid storage of larval oenocytes.